2021
DOI: 10.15420/ecr.2021.27
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Disease in Patients with Aortic Stenosis and Transcatheter Aortic Valve Implantation: Implications for Management

Abstract: Aortic valve stenosis (AS) is the most common valvular heart disease among elderly patients. Since the pathophysiology of degenerative AS shares common pathways with atherosclerotic disease, the severity of AS in the elderly population is often concurrent to the presence of coronary artery disease (CAD). Although surgical aortic valve replacement has been the standard treatment for severe AS, the high operative morbidity and mortality in complex and fragile patients was the trigger to develop less invasive tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 66 publications
0
6
0
1
Order By: Relevance
“…Given these studies and other observational and retrospective studies, it does appear that the presence of CAD is associated with worse outcomes in some subgroups of TAVI patients with complex CAD and high SYNTAX scores [14,15] , and revascularization with PCI does improve intermediate and long-term mortality. However, the benefit of PCI needs to be individualized.…”
Section: Prognostic Role Of Cad In Patients Undergoing Tavimentioning
confidence: 83%
“…Given these studies and other observational and retrospective studies, it does appear that the presence of CAD is associated with worse outcomes in some subgroups of TAVI patients with complex CAD and high SYNTAX scores [14,15] , and revascularization with PCI does improve intermediate and long-term mortality. However, the benefit of PCI needs to be individualized.…”
Section: Prognostic Role Of Cad In Patients Undergoing Tavimentioning
confidence: 83%
“…The endothelialization process varies in time and completeness depending on the device size and type [13] and while theoretically, this may represent a concern for device thrombosis, currently there is no clear evidence that antithrombotic therapy has a true clinical impact [14]. On the other hand, it is well established that after TAVI patients are exposed to a higher and temporally variable risk of ischemic events, including transient ischemic attack (TIA), stroke, myocardial infarction (MI) [15][16][17][18][19][20][21][22][23][24] and valve thrombosis [25,26]. Hence, evaluating the impact of different antithrombotic strategies to mitigate this risk has been the core focus of multiple clinical studies.…”
Section: Rationale For Antithrombotic Therapy After Tavimentioning
confidence: 99%
“…To date, TAVI is recommended in older patients (>75 years), or in those who are high risk (STS-PROM/EuroSCORE II >8%) (3). Several studies have demonstrated the association between AS and coronary artery disease (CAD), which increases with the age, as the risk factors for aortic stenosis are similar to those for atherosclerotic disease (4). Specifically, CAD has been reported in ≥50% of AS patients undergoing both SAVR and TAVI (5).…”
Section: Judge a Man By His Questions Rather Than His Answersmentioning
confidence: 99%